Analisis Produksi Padi Di Desa Selodakon Kecamatan Tanggul Kabupaten Jember - Rakryan Hanung Waskito; Herman Cahyo Diartho; Duwi Yunitasari (Jurnal Ekuilibrium, 2021)
Rice is one of the result of agriculture from food crop sub sector. Rice is the most important food crop for human being, especially the people of Indonesia. Rice is a food source of carbohydrate and contains nutriens that are needed by human body. Tanggul Subdistrict is one of the district rice harvesters in Jember Regency, East Java. This research aims to analyze rice production produced in tanggul subdistrict, jember regency. Variables used in this research are land area, labor, fertilizer, and pesticide. To support the data in this study using primary data. Analytical method used is the Cobb - Douglas production function, to facilitate the estimation of the equation is expanded generally and coverted to multiple linear form. Based on the result of analysisof land area variables, labor, fertilizer, and pesticide have a positive and significant effect on rice production in Tanggul Subdistrict, Jember Regency, East Java.